2010
DOI: 10.2903/j.efsa.2010.1789
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Polybrominated Biphenyls (PBBs) in Food

Abstract: EFSA was asked by the European Commission to deliver a scientific opinion on polybrominated biphenyls (PBBs) in food. PBBs are additive flame retardants which were applied in synthetic fibres and polymers. PBBs are present in the environment at low concentrations and likewise in biota and in food and feed. Data from the analysis of 16 PBB congeners in 794 food samples were provided to EFSA by 6 Member States, covering the period from 2003 to 2009. Toxicity studies were carried out with technical PBB mixtures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 197 publications
(266 reference statements)
0
5
0
Order By: Relevance
“… Panel on Contaminants in the Food Chain (CONTAM): publication of a number of opinions involving case‐by‐case approaches to risk assessment of multiple contaminants. Component‐based approaches have included Toxic Equivalency Factors (TEF) approaches for non‐ortho polybrominated biphenyls and several groups of marine biotoxins (EFSA CONTAM Panel, 2009 , 2010 ). Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF): risk assessment of combined exposure to rum ether [Flavouring Group Evaluation 500 (FGE.500)] and grouping of 84 reported constituents for 12 congeneric groups allocated based on structural and metabolic similarity (EFSA CEF Panel, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Panel on Contaminants in the Food Chain (CONTAM): publication of a number of opinions involving case‐by‐case approaches to risk assessment of multiple contaminants. Component‐based approaches have included Toxic Equivalency Factors (TEF) approaches for non‐ortho polybrominated biphenyls and several groups of marine biotoxins (EFSA CONTAM Panel, 2009 , 2010 ). Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF): risk assessment of combined exposure to rum ether [Flavouring Group Evaluation 500 (FGE.500)] and grouping of 84 reported constituents for 12 congeneric groups allocated based on structural and metabolic similarity (EFSA CEF Panel, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Panel on Contaminants in the Food Chain (CONTAM): publication of a number of opinions involving case‐by‐case approaches to risk assessment of multiple contaminants. Component‐based approaches have included Toxic Equivalency Factors (TEF) approaches for non‐ortho polybrominated biphenyls and several groups of marine biotoxins (EFSA CONTAM Panel, 2009 , 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other BFRs addressed here are decabromobiphenyl (BB-209), decabromodiphenyl ethane (DBDPE), hexabromobenzene (HBB), and a brominated intermediate currently used in the BFR production and natural product (i.e., 2,4,6-tribromophenol; 2,4,6-TBP) all of which are reviewed and assessed by EFSA 2010-2012. ,, In 1976, the US stopped production of BB-209, but BB-209 continued to be produced in Europe (France) until 2000 . DBDPE was introduced as a replacement for decabromodiphenyl ether (BDE-209) and has been on the market for more than 20 years .…”
Section: Introductionmentioning
confidence: 99%
“…A significant decrease in K values was observed for 14 days exposure to BB-80 in the 10 and 50 μg/L treatment groups (Table S7), indicating that the fish condition was worsened by BB-80. The administration of PBBs during early pregnancy in rats was reported to cause offspring with lower survival rate and malformations …”
Section: Resultsmentioning
confidence: 99%
“…After 14 days exposure and 7 days discontinued exposure, there was no statistical significance for TSH changes for OH-BB-80, while a significant decrease was observed in the BB-80 group (Figure C). Previous evidence indicated that exposure to PBBs decreased the serum T3/T4 levels and increased the TSH level in rodents . An excessive amount of THs is harmful to zebrafish larval development and may cause impaired growth of both pectoral and pelvic fins as well as severely defected development, particularly the inhibited development of scales and pigment patterns …”
Section: Resultsmentioning
confidence: 99%